A new uranyl carboxylate constructed from a semi-rigid tetracarboxylic acid ligand containing two iminodiacetic acid moieties and four methyl groups. Issue 9 (25th June 2021) - Wang, Zhong; Hou, Xiaomin; Tang, Si-Fu
Abstract: One new uranyl tetracarboxylate, [UO2 (H2 L 3 )(H2 O)]·3H2 O, was synthesized hydrothermally from a methyl group decorated semi-rigid tetracarboxylic acid ligand and systematically characterized using powder and single-crystal X-ray diffraction, IR, EA, TGA, and luminescent methods. The four carboxylate groups in the carboxylic ligand were all monodentate bridging and the uranyl cations are linked by tetracarboxylic ligands to form a two-dimensional layered crystal structure. Introduction of methyl groups has a large effect on the speciation of uranyl carboxylates. The thermal behavior and luminescent properties are also investigated. Graphical Abstract: UF0001